2017
DOI: 10.5194/hess-21-4073-2017
|View full text |Cite
|
Sign up to set email alerts
|

Waning habitats due to climate change: the effects of changes in streamflow and temperature at the rear edge of the distribution of a cold-water fish

Abstract: Abstract. Climate changes affect aquatic ecosystems by altering temperatures and precipitation patterns, and the rear edges of the distributions of cold-water species are especially sensitive to these effects. The main goal of this study was to predict in detail how changes in air temperature and precipitation will affect streamflow, the thermal habitat of a cold-water fish (the brown trout, Salmo trutta), and the synergistic relationships among these variables at the rear edge of the natural distribution of b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 114 publications
(136 reference statements)
0
25
0
Order By: Relevance
“…Historical simulations were performed for procedure quality control (by comparing modelled versus observed data). The daily results of this local scale modelling are presented in Santiago, Muñoz‐Mas, et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historical simulations were performed for procedure quality control (by comparing modelled versus observed data). The daily results of this local scale modelling are presented in Santiago, Muñoz‐Mas, et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The literature on trout physical habitat structure is extensive (Armstrong, Kemp, Kennedy, Ladle, & Milner, 2003); however, only recently have the joint effects of flow and temperature been addressed to assess the persistence probability of affected trout populations (e.g., Muñoz‐Mas et al, 2016, 2018; Wenger et al, 2011). Santiago, Muñoz‐Mas, et al (2017) also showed that the synergistic effects of both thermal and hydrological changes (namely, stream temperature increase and streamflow reduction) will exacerbate suitable habitat loss for cold‐water species such as brown trout because streamflow reductions may increase stream thermal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact may be expressed differently among rivers, even in the same geographic area. Investigations in central Spain (Santiago et al, ) examining the viability of brown trout ( Salmo trutta L.) habitat in response to climate change illustrate how this response can vary among catchments depending on physical attributes. Projected reductions in streamflow (max.…”
Section: River Biota Responsementioning
confidence: 99%
“…In the Pacific Northwest, in particular, assessments of climate variability and projections of climate change in forested headwaters are important owing to the dominance of these drainages in the landscape, and their importance to multiple downstream and upland ecosystem services-yet we are just beginning to understand climate influences on forested headwater streams. Stream-temperature and streamflow changes are attributes often considered in watershed studies of climate change, as these factors affect stream ecological conditions and functions, especially species habitat suitability via myriad ecophysiological constraints [38,39,43]. In the Northwestern US more generally, at larger scales (i.e., larger landscapes and watersheds), climate projections include warmer temperatures [44][45][46][47] and altered precipitation patterns such as reduced snowpack-especially at low-to-mid elevations [48,49], which have many headwater basins in the region.…”
Section: Introductionmentioning
confidence: 99%